Application of HACCP to improve the safety of informally marketed raw milk in Kenya - Mwangi, A.; Arimi, S.M.; Mbugua, S.; Kang'ethe, Erastus K.; Ouma, Emily A.; Omore, Amos O.; McDermott, John J.; Staal, Steven J. (International Society for Veterinary Epidemiology and Economics, 2000)
Food safety standards require monitoring from production-to-consumption. The Hazard Analysis Critical Control Points (HACCP) process, recommended by FAO/WHO, is now a widely accepted methodology in risk analysis for industrially processed foods. HACCP identifies the points in a process that are hazardous, their risk factors and potential level of risk so that "critical control points" for remedial action can be implemented Controls are specific actions taken to prevent hazards. The application of HACCP is a major challenge in developing countries where food markets are mostly informal. Market channels for milk range from direct sales of liquid milk or processed dairy products from producers to consumers, to a long chain involving combinations of private traders on bicycle, public or private transport, milk bars and kiosks, dairy farmer groups, small-scale and industrial processors. About 88% of marketed milk in Kenya is sold unprocessed, outside regulated channels. This study attempts to adapt a HACCP methodology to assess health risks at different points in the informal dairy marketing network.